The Right to Climate Adaptation - Byskov, Morten Fibieger (Ethical theory and moral practice, 2024)
The Intergovernmental Panel for Climate Change has over the past decade repeatedly warned that we are heading towards inevitable and irreversible climate change, which will negatively affect the lives, livelihoods, and well-being of millions of people around the world, both at present and in the future. In fact, many people, especially vulnerable and marginalized communities in low- and middle-income countries, already live with the effects of climate change in their daily lives. While adaptation - along with mitigation and compensation for loss and damage as a consequence of climate change - was identified as the central pillars of a just climate policy in the Paris Agreement it is unclear whether this entails a right to adaptation - that some people are owed, as a matter of justice, to have the ability to adapt to climate change - and, if so, what such a right would look like. In this paper, I argue that individuals and communities who are or will be negatively affected by climate change through no fault of their own should have the right to adaptation. I argue that the right to adaptation should be specified through four questions: (i) who has a right to adaptation; (ii) what is it a right to; (iii) how much is it a right to; and (iv) who has the duty to uphold the right to adaptation?